: GAMBARAN PENGGUNAAN ANTIBIOTIK PADA PASIEN ULKUS DIABETIKUM DI INSTALASI RAWAT JALAN PENYAKIT DALAM RSUD ULIN BANJARMASIN PERIODE JULI – DESEMBER 2018 - Saftia Aryzki; Merry Alicia; Siti Rahmah (Jurnal Ilmiah Manuntung, 2020)
Diabetic ulcers are a disease that is experienced by many people with diabetes mellitus, open wounds on the skin surface of the diabetic ulcer have the potential to develop into infection, to deal with the problem of infection needed the right treatment, one of them is by using antibiotics. The purpose of this study was to describe the use of diabetic ulcer patients In Installation Of Outpatient in RSUD Ulin Banjarmasin Period July-December 2018. This study is a non-experimental study with a descriptive type of study through a retrospective search for outpatient prescription for diabetic ulcers. This research was conducted in April-May 2019 in Installation Of Outpatient in RSUD Ulin Banjarmasin. Sampling is done by saturation sampling method, the population in this study were 254 prescrptions. While the sample in this study were 228 prescrptions that met the criteria of inclusion and exclusion. The data obtained is copied to the observation sheet, after the data collected is then entered into a computer and a calculation is carried out to find out the percentage of each factor studied and finally the data will be presented in table form. The results obtained from the study of 228 prescriptions of diabetic ulcer patients obtained the use of single antibiotics as much as 182 (79.82%) and combination antibiotics by 46 (20.18%). The single most prescribed group of antibiotics is the Makrolide group of 49.56%, the Makrolide group which is often prescribed namely Clindamycin 300 mg as much as 39.91%.While the most prescribed combination of 2 antibiotics is Clindamycin 300 mg + Metronidazole 500 mg 14.47%.